2021
DOI: 10.1097/ta.0000000000003506
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of trauma care: Associations of race, insurance status, and place on opioid prescriptions, postdischarge referrals, and mortality

Abstract: BACKGROUND:Racial disparities in trauma care have been reported for a range of outcomes, but the extent to which these remain after accounting for socioeconomic and environmental factors remains unclear. The objective of this study was to evaluate the unique contributions of race, health insurance, community distress, and rurality/urbanicity on trauma outcomes after carefully controlling for specific injury-related risk factors. METHODS:All adult (age, ≥18 years) trauma patients admitted to a single Level I tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Of these publications, 4,104 were excluded and 74 articles were included (Supplemental Digital Content, Supplementary Figure 1, http://links.lww.com/TA/D174). 2–76 A bimodal distribution shows that location and access disparities represented the majority of articles, followed by age and race (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these publications, 4,104 were excluded and 74 articles were included (Supplemental Digital Content, Supplementary Figure 1, http://links.lww.com/TA/D174). 2–76 A bimodal distribution shows that location and access disparities represented the majority of articles, followed by age and race (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…5 One study reveals trauma-related deaths could be linked to racial disparities in the care of Black patients. 7 Similarly, studies have shown that a lack of insurance, especially in under-represented pediatric patients, is linked to higher mortality after trauma, and can also be predictive of outcomes in adults such as post-hospitalization care and disposition. 2 Additional studies have demonstrated how disparities in sex/gender, access to care, age, and health literacy interact to cause similar discrepancies in outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S ocial and structural determinants of health have a major impact on outcomes after traumatic injury, 1 often outstripping the role of acute medical care. 2 Clinicians and health systems are striving to address these societal inequities to improve outcomes for trauma patients. 3,4 Some of these health-harming social factors have legal remedies, and attorneys or other trained legal advocates could support patient health by applying existing legal protections and resources.…”
mentioning
confidence: 99%
“…Trauma patients are also frequently negatively influenced by legal structures like policing, firearm violence, and involvement with the legal system. 2 In addition, trauma patients may benefit from legal access to state compensation policies that provide funds for victims of violence or crime. Trauma patients and trauma systems of care therefore stand to benefit from addressing health-harming legal needs.…”
mentioning
confidence: 99%